Introduction and Training of Database Systems for Vocational High School Students in Palembang City - Evi Yulianingsih; Febriyanti Panjaitan; Fatmasari; Helda Yudiastuti; Nurul Adha (PT FORMOSA CENDEKIA GLOBAL, 2022)
In ICT needed to learn database management. One application in database management is MySQL. The service team conducted an analysis of the community's needs regarding the application of the ICT application, especially at SMKs in the city of Palembang. In practice, service participants at SMK are accompanied by tutorials where the presenters conduct demonstrations by working on the material that has been prepared, which then the participants follow and implement the material simultaneously with the presenters. In the end, the service team found that the participants had gained knowledge and skills from this training activity. This can be seen from the feedback given by the participants where 78% of the participants stated that they understood the material provided well and the material presented was very useful.